Plans to Live on a Reservation Following College Among American Indian Students: An Examination of Transculturation Theory - Terry E. Huffman (Journal of Research in Rural Education, 2011)
This paper focuses on American Indian college students and uses transculturation theory to examine factors related to selfreported plans to live on a reservation following completion of college. Transculturation theory assumes a strong cultural identity is fundamental to academic success. The author uses the basic premise of this perspective to consider an extension to its assumptions. Findings indicate that an implied assumption of the transculturation perspective is that American Indians closely aligned with traditional culture tend to seek careers in which they serve Native communities and more likely plan to live on a reservation after college.